Impact of Positive Interferon-Gamma Release Assay on IVF-ET Pregnancy Outcomes in Infertile Patients With Untreated Prior Tuberculosis: A Prospective Cohort Study - Gai, Xiaoyan; Chi, Hongbin; Zeng, Lin; Cao, Wenli; Chen, Lixue; Zhang, Chen; Li, Rong; Sun, Yongchang; Qiao, Jie (Frontiers in Medicine, 2021)
Introduction: Tuberculosis (TB) is a major infectious disease that seriously endangers human health and female reproduction. In our previous study, 10.4% of infertile patients preparing for In vitro fertilization and embryo transfer (IVF-ET) had prior pulmonary TB (PTB) as detected on chest X-ray (CXR) screening. Among them, 81.8% did not receive anti-TB treatment. It remains unclear whether infertile women with untreated prior PTB have latent TB infection (LTBI) and whether LTBI affects IVF-ET outcomes. In this study, we aim to analyze the relationship between LTBI and pregnancy outcomes following IVF-ET in patients with untreated prior PTB. Methods and Analysis: We designed a prospective cohort study of 1,200 infertile women with CXR findings suggestive of old-healed untreated TB, who are preparing for IVF-ET. Patients with a history of active TB and anti-TB treatment will be excluded. Interferon-gamma release assay (IGRA) will be used in patients with CXR findings suggestive of old-healed untreated TB to construct a cohort of IGRA-positive and IGRA-negative patients. Participants will undergo IVF-ET. General information, including age, body mass index, infertility causes, and controlled ovarian hyperstimulation protocol, will be recorded. Participants will be followed up during pregnancy. The primary outcome is live birth. Secondary outcomes include the numbers of retrieved oocytes, high-quality embryo rate, clinical pregnancy, number of active TB cases during pregnancy, and miscarriage. Ethics and Dissemination: The study was approved by the Ethics Committee of Peking University Third Hospital [approval number (2020)218-01; approval date: June 19, 2020]. The research results will be disseminated through scientific/medical conferences and published in academic journals. Trial Registration:ClinicalTrials.gov; identifier: NCT04443283.